1H NMR relaxation and theoretical calculation study on Tris(pentafluorophenyl)borane as a catalyst in preparation of Poly(carborane-siloxane) polymers. (February 2019) - Lou, Pingping; Zhang, Xuezhong; Tan, Yongxia; Zhang, Zhijie; Bian, Wensheng; Ma, Haitao; Xie, Zemin
Abstract: Poly(carborane-siloxane) polymers were successfully synthesized by tris(pentafluorophenyl)borane catalyzing diorganohydroxysilanes (SiOH) and dihydrosilanes (SiH) to form siloxane bond and release hydrogen. The structure of monomers and polymers were characterized by 1 H, 13 C, 29 Si NMR and FI-IR. Furthermore, in the present study, the qualitative characterization of silicon hydrogen bond in dihydrosilanes activated by catalyst B(C6 F5 )3 was investigated by 1 H NMR relaxation test and theoretical calculation. The results shown that silicon hydrogen bond (SiH) and B(C6 F5 )3 form the complex [Si⋯H⋯B(C6 F5 )3 ] which is relevant to chemical reactivity. In addition, dihydrosilanes exhibit the following reactive activity order: 1, 1, 3, 3-tetramethyldisiloxane > 1, 7-bis(3-hydridotetramethyldisiloxanyl)- m -carborane > diphenylsilane > methylphenylsilane > 1, 7-bis(dimethylsilyl)- m -carborane. This synthetic method offers a new effective approach to synthesize poly(carborane-siloxane) polymers and the reactive activity order has a guide significance for experimental system design. Highlights: B(C6 F5 )3 was an efficient catalyst in synthetizing poly(carborane-siloxane) by catalyzing Si-OH and Si-H. The interaction between dihydrosilane and catalyst was examined by 1 H NMR relaxation and theoretical calculation. The reactive activity order of dihydrosilanes has a guide significance for experimental system design. 1 H NMR relaxation and theoretical calculation methods employed provide a useful tool to investigate chemical reactivity.